2010
DOI: 10.3109/14767051003678135
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of induction of labour using maternal characteristics, ultrasound assessment and biochemical state of the cervix

Abstract: The combination of sonographic assessment of the cervix and maternal characteristics was superior to the either BS or CL alone in the prediction of the induction outcome. Inclusion of the absence/presence of phIGFBP-1 did not further improve induction outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
5
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 26 publications
1
25
5
4
Order By: Relevance
“…These results, are limited because in these two models, they did not distinguish between cesarean performed for failed induction and cesarean section for other reasons as we did in our study. Neither Cheung et al [30] classiWed cesarean sections to assess preinduction sonographic, digital examination and biochemical changes in the cervix to predict induction outcome.…”
Section: Discussionmentioning
confidence: 98%
“…These results, are limited because in these two models, they did not distinguish between cesarean performed for failed induction and cesarean section for other reasons as we did in our study. Neither Cheung et al [30] classiWed cesarean sections to assess preinduction sonographic, digital examination and biochemical changes in the cervix to predict induction outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Por el contrario, en nuestro estudio, la paridad fue el factor con mayor capacidad predictiva en el resultado de parto. Por ello, decidimos integrarlo en los nuevos índices, coincidiendo con varios autores que también incorporaron la paridad en sus modelos predictivos en gestantes con IDP [10][11][12][15][16][17] . En este sentido, Dhall y col 18 intentaron en 1987 introducir el parámetro de la paridad en una nueva escala formada además por dilatación, borramiento y consistencia.…”
Section: Discussionunclassified
“…Esta nueva modificación se justificó porque la paridad puede modificar de forma relevante la probabilidad de parto [10][11][12] . Con ella, el índice pasó a tener una puntuación máxima de 15 puntos, aunque el estudio no aportó información sobre su capacidad predictiva.…”
unclassified
“…[92][93][94][95][96] The biochemical markers (phIGFBP-1) in cervical secretions were assessed in preinduction but did not seem to improved the prediction of induction outcome. 90 Results from 2006 showed that ultrasound assessment of fetal head-perineum distance was predictive of labor outcome for women with prelabor rupture of membranes at term. 96 In 2008, Eggebø et al in a prospective study of 275 women admitted for induction of labor 97 aimed to compare this distance (measured by transperineal ultrasound as the shortest distance from the outer bony limit of the fetal skull to the skin surface of the perineum) with maternal factors, Bishop score and ultrasound measurements of cervical length, cervical angle and occiput position (assessed by transabdominal ultrasound imaging).…”
Section: Prediction When Planning Induction Of Labormentioning
confidence: 98%
“…However, in most clinics, and in most of the patients, the Bishop score 86 for more than 4 decades is still the 'gold standard' for assessing the prognostic of induction of labor, although is considered a subjective evaluation with limitations. 87 Transvaginal cervical length [88][89][90] or angle measurement 91 improved the prediction rate of the outcome of induction. Preinduction measurement of the cervical length increases the odds of cesarean section by about 10% for each 1 mm increase above 20 mm and the odds are about 75% lower in multiparae compared with nulliparae with the same cervical length.…”
Section: Prediction When Planning Induction Of Labormentioning
confidence: 98%